Memorandum of understanding between Universiti Teknologi MARA and Diabetes Malaysia / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on cooperation and promotion to produce modules/guide for diabetes patient support and empowerment group (Dream program by Asrazeneca).